An ancient integration in a plant NLR is maintained as a trans-species polymorphism - Brabham, Helen J; Inmaculada Hern ndez-Pinz n; Holden, Samuel; Lorang, Jennifer; Moscou, Matthew J (bioRxiv, 2018)
Plant immune receptors are under constant selective pressure to maintain resistance to plant pathogens. Nucleotide-binding leucine-rich repeat (NLR) proteins are one class of cytoplasmic immune receptors whose genes commonly show signatures of adaptive evolution. While it is known that balancing selection contributes to maintaining high intraspecific allelic diversity, the evolutionary mechanism that influences the transmission of alleles during speciation remains unclear. The barley Mla locus has over 30 described alleles conferring isolate-specific resistance to barley powdery mildew and contains three NLR families (RGH1, RGH2, and RGH3). We discovered (using sequence capture and RNAseq) the presence of a novel integrated Exo70 domain in RGH2 in the Mla3 haplotype. Allelic variation across barley accessions includes presence/absence of the integrated domain in RGH2. Expanding our search to several Poaceae species, we found shared interspecific conservation in the RGH2-Exo70 integration. We hypothesise that balancing selection has maintained allelic variation at Mla as a trans-species polymorphism over 24 My, thus contributing to and preserving interspecific allelic diversity during speciation.